Pengembangan Metode Contrast Stretching Pada Media Pembelajaran Geografi Berbasis Pengolahan Citra Digital - Alexius Endy Budianto; Yuli Ifana Sari; Ika Meviana (LPPM STIKI MALANG, 2023)
The development of digital image-based learning media for rock/soil geography learning is a tool for learning activities so that students can understand more easily, not watch, so that they are expected to be more innovative in packaging interesting subject matter with digital technology. The aims of this researcher are: (1) to create innovative learning media with digital imagery technology (2) to know the classification of various types of rock/soil with a system for detecting rock types using digital imagery, (3) to find out the level of feasibility of developing geography-based learning media Digital Image, (4) Knowing the effectiveness of using Digital Image geography learning media. The development model used in this research is Research and Development. To produce this learning media, the researcher developed it using the dhelpi programming language and in the contrast stretching process which can process data: save, update material, delete and load images in the form of images in BITMAP form so that they are stored in the testing data base. While the research subjects were lecturers and students of geography education at the University of PGRI Kanjuruhan Malang. The target of this research is to produce: 1) a learning model along with its curriculum that is able to adapt digital image processing; 2) increasing lecturer innovation in modifying learning media; 3) scientific articles. Lecturer competence will increase by creating media applications based on digital image processing, and at the same time changing the mindset of lecturers and students.